The Eye of War : Military Perception from the Telescope to the Drone - Bousquet, Antoine J. (Book collections on Project MUSE., 2018)
"This project explores how technologies of perception -- the ability to detect and to avoid detection -- have transformed modern warfare. The book spans from the Renaissance, where the rationalization of vision and space started to influence military strategy, to the present day, where combatants increasingly face off in the perceptual realm of drones and satellites as much the physical battlefield. Each chapter explores a different perceptual theme: sensing, imaging, mapping and hiding"--